PROFIL 24 JAM KUAT PENERANGAN, SUHU UDARA, KELEMBABAN UDARA DI LUAR DAN DI DALAM HUTAN MANGROVE - Dalengkade, Mario Nikolaus (PATTIMURA UNIVERSITY, 2020)
The phenomenon of climate change that occurs in statistical distribution patterns throughout the period of change in variation. These changes would be implications for micro abiotic conditions. As a case study, the abiotic condition profile in mangrove ecosystems is interesting to study in the Fourier function. This study aims to describe the relationship between weather variables such as intensity, air temperature, and humidity using the Fourier function . The results of the study showed that the intensity of position 1 (the outermost point) and position 3 (the edge point) presented a graphic higher than position 9 (the point in) the mangrove forest, with a peak illumination at 12.00 at 51,210 lux. The air temperature at 19.00‒04.00 has decreased and rises again until 13.00 o’clock reached a maximum point of 34,60 C. The air temperature is inversely proportional to the humidity, at 19.00 to 04.00 an increase and again decreased to reached the minimum limit of 59,9% at 13.00 o’clock. In addition, cross-correlation showed of the air temperature and humidity consistently presented thermal diffusion of 1,0 hours from position 1 to position 3, while positions 3 to position 9 are 1,0 hours ‒ 1,2 hours. Data indicate that mangrove forests can reduce vertical thermal diffusion.